Screening of Potent Arsenic Resistant and Plant Growth Promoting Bacillus species from the Soil of Terai Region of Nepal - Poudel, Pramod; Nepal, Ashish; Magar, Rashmi Roka; Rauniyar, Pratibha; Magar, Lil Buda (Tribhuvan University Journal of Microbiology, 2019)
Objectives: To isolate arsenic resistant Bacillus spp. and to determine plant growth promoting activities. Methods: Eighteen soil samples were collected from the agricultural soil of Terai region of Nepal. Selective isolation of Bacillus species was done by heating the soil at 80 ºC for 15 minutes before the isolation. Nutrient agar was used as an isolation medium. Screening of arsenic resistant Bacillus species was done using nutrient agar supplemented with 100 ppm sodium arsenate and sodium arsenite. For plant growth promoting activity; IAA production was detected taking 0.1% tryptophane and measuring absorbance at 540 nm, NH3 production was tested by Nessler’s reagent and phosphate solubilization activity was detected by growing colonies on Pikovskaya’s agar. Sugar assimilation test was performed to identify the isolates. Most potent arsenic resistant isolate was identified by 16S rRNA gene sequencing. Results: Among 54 randomly selected isolates, 42 were found to be Gram-positive rod-shaped, spore-forming while 12 isolates were Gram-negative bacteria. The isolates IN12a, M12a and BG34a showed growth on 100 ppm sodium arsenite containing NA. Only isolate M12a tolerated up to 1000 ppm and 15000 ppm of sodium arsenite and sodium arsenate respectively, while other isolates could not grow above 400 ppm sodium arsenite. The isolates IN12a and M12a were able to produce IAA and solubilize phosphate while BG34a could not. Both the isolates IN12a and M12a were able to utilize the sugars glucose, fructose, lactose, sucrose, galactose, mannose, mannitol, maltose and xylose. Based on the 16S rRNA gene sequencing, isolate M12a was identified to be Bacillus flexus with highest similarity of 99.2%. Conclusion: Arsenic resistant and plant growth promoting Bacillus spp. was isolated from the agricultural soil of Terai region of Nepal